Photosynthetic characteristics and chlorophyll content of Cypripedium japonicum in its natural habitat. Issue 4 (2nd October 2022) - Kim, Dong-Hak; Son, Sungwon; Jung, Ji-Young; Lee, Jea-Cheon; Kim, Pan-Gi
Abstract: This study characterizes the growth conditions of Cypripedium japonicum Thunb. (Korean lady's slipper), a rare and endangered plant, across three different sites in its natural habitat. The three natural habitats of C. japonicum had different canopy densities that influenced the relative light intensity and quality (R/FR ratio) on the forest floor, the values of which, decreased with the increase in canopy density. The leaf mass per area of C. japonicum increased with an increase in canopy openness, and the difference in growth due to increased light availability was further confirmed by the chlorophyll content. Higher values of the average daily photosynthetic activity, transpiration rate, and stomatal aperture were recorded in C. japonicum growing in natural habitats that received a higher frequency of sunflecks. The activities of the photosystem and carbon fixation of the plants growing in the three habitats were compared through the light-response and A–Ci curves, and it was found that their photosynthetic capacity decreased in a low light environment. The growth and physiological characteristics of C. japonicum growing in different habitats were dependent on the light conditions in the stand, and therefore, increasing the light availability by control of canopy density may improve the propagation of C. japonicum . We believe that the findings of our study will facilitate the prediction of population dynamics and the long-term conservation and restoration of C. japonicum .